Conceptualizing Ryff's Psychological Well-being Model with Confucian Perspective - Choi, Saeeun; Choi, Seulki (한국사회학, 2016)
The objective of this study is to explore how the contours of psychological well-being, as described by Ryff’s six-dimensional model, might differ in the Korean context. We tried to apply Ryff’s six-dimension psychological well-being model in Korean case by considering the Confucianism. To fulfill this goal, first, we briefly reviewed the theoretical background and themes of Ryff’s psychological well-being model. Second, we suggested themes of psychological well-being based on the Confucian perspective. Next, we reviewed the psychometric studies in Korea on Ryff’s psychological well-being scale and corresponding empirical studies using Ryff’s model. Last, we discussed the implication of culturally-relevant theoretical framework on psychological well-being in the later life in Korea. In conclusion, we suggest that the constructs of autonomy and environmental mastery are relevantly weak in Confucius perspective whereas the positive relations with in particular family relations are strong in understanding the psychological well-being of the elderly.